Chapter Polyimide Films for Digital Isolators - Diaham, Sombel (InTechOpen, 2020)
Digital isolators provide compelling benefits over legacy opto-couplers in terms of high speed, low power consumption, high reliability, small size, high integration, and ease of use. Billions of digital isolators using micro-transformers have been widely adopted in many markets including automotive, industry automation, medical, and energy. What are essential for the high voltage performance for these digital isolators are polyimide films deposited in between the top spiral winding and bottom spiral winding for the stacked winding transformers. In this chapter, digital isolator construction using polyimide films as isolation layers will be reviewed. To meet various safety standards such as UL and VDE, digital isolators need to satisfy various high voltage performances, such as short duration withstand voltage, surge voltage, and working voltage. Polyimide aging behavior under various high voltage waveforms such as AC or DC was studied, and isolator's working voltage is extrapolated through a polyimide lifetime model. Structural improvements to improve polyimide high voltage lifetime will also be discussed.